Amelioration of urban temperature through landscape design approaching hot-humid climate: a review / Sharifah Khalizah Syed Othman Thani, Nik Hanita Nik Mohamad and Sabrina Idilfitri. - Syed Othman Thani, Sharifah Khalizah; Nik Mohamad, Nik Hanita; Idilfitri, Sabrina (Universiti Teknologi MARA Cawangan Selangor, 2018)
This paper discusses a conceptual review of sustainable landscape design approach as mitigating strategies to modify urban temperature in a hot- humid climate.The amelioration of urban temperature through landscape approach can be achieved by incorporating sustainable landscape design practices via the interplay of natural vegetation in the hot-humid tropics. The findings of this paper are hoped to guide the practitioners in landscape architecture, policy makers and urban designers to incorporate sustainable landscape design approach towards improving outdoor thermal comfort; thus providing a better quality of life.